Descripción de una colonia mixta de aves acuáticas en Laguna Iberá, Corrientes, Argentina - Parera, Anibal (1996)
In the breading season 1991-1992 a mixed water-bird colony of about 400 nests of Egretta thula. Casmerodius albus. Nycticorax nycticorax. Ardea cocoi and Anhinga anhinga appeared at Laguna Iberá, Corrientes Provinee, Argentina. It was unique for its type in the arca, Observations were carried out during two breeding seasons. The dominant species during the first season was E, thula (52.5 %ofthe nests) followed by C. albus, During the next season the colony expanded in area and in number ofnests (87 %). The dominant speeies was now C. albus, with 80,5 %of the nests and a growth of399 %. AII the remaining speeies declined, andN. nycticorax was apparently absent. Evaluation ofthe impaet ofhuman visitors on the eolony require further monitoring.